An investigation into factors influencing the quality of nursing care in district hospitals in the West Coast Winelands region of the Western Cape - Eygelaar, Johanna Elizabeth (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MCur (Nursing Science))--University of Stellenbosch, 2009.